Analysis of Domestic Component Level (TKDN) and Company Benefit Weight (BMP) in Construction Projects - Dwi Lutfil Khakim; I Nyoman Dita Pahang Putra (International Journal of Mechanical, Electrical and Civil Engineering, 2024)
In the world of construction projects, good project management is required, including the use of domestic products. The government encourages the use of domestic products through the program to increase the use of domestic production (P3DN). The amount of domestic content in commodities, services, and the combination of products and services can be used to measure the use of domestic products. This quantity is called the Domestic Component Level (TKDN). Company Benefit Weight (BMP) is an award given to industrial companies that invest and produce in Indonesia. This research aims to calculate the amount of TKDN and BMP for the Muhammadiyah Ahmad Dahlan Kediri Hospital construction project. With reference to the Ministry of Industry of the Republic of Indonesia's Regulation No. 16 of 2011 regarding Provisions and Procedures for Calculating Domestic Component Levels, the research employs a descriptive quantitative methodology to compute and analyze Domestic Content Levels (TKDN). The results of analytical calculations show that the TKDN percentage is 69.65% and the BMP percentage is 3%. This research concluded that the total TKDN and BMP was 72.65%, thus meeting the minimum limit for the sum of TKDN and BMP of 40%.